2023
DOI: 10.1111/spc3.12792
|View full text |Cite
|
Sign up to set email alerts
|

Who do we trust? Differences in types of trust and beliefs in conspiracy theories between vaccinated and unvaccinated Europeans across 17 European countries

Abstract: A plethora of research has highlighted that trust in science, political trust, and conspiracy theories are all important contributors to vaccine uptake behavior. In the current investigation, relying on data from 17 countries (N = 30,096) from the European Social Survey we examined how those who received (and wanted to receive the COVID‐19 vaccine) compared to those who did not differ in their trust in: science, politicians and political parties, international organizations and towards people in general. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Within the anti-elite literature, anti-intellectualism has been found to help explain concern about COVID-19 and social distancing behavior (Merkley and Loewen 2021), and vaccine hesitancy has been found to be predicted by anti-elite worldviews (Stoeckel et al 2022), conspiracy beliefs (Syropoulos and Gkinopoulos 2023), and populist attitudes more generally (Juen et al 2021;Edwards et al 2021). The common explanation within this research is that populists, anti-elitists, or antiintellectuals distrust scientific experts and established political institutions.…”
Section: System Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the anti-elite literature, anti-intellectualism has been found to help explain concern about COVID-19 and social distancing behavior (Merkley and Loewen 2021), and vaccine hesitancy has been found to be predicted by anti-elite worldviews (Stoeckel et al 2022), conspiracy beliefs (Syropoulos and Gkinopoulos 2023), and populist attitudes more generally (Juen et al 2021;Edwards et al 2021). The common explanation within this research is that populists, anti-elitists, or antiintellectuals distrust scientific experts and established political institutions.…”
Section: System Trustmentioning
confidence: 99%
“…Studies have also found that trust in government is associated with attitudes and behaviors specifically related to the COVID-19 pandemic. While studies explaining threat appraisals have found mixed evidence (Devine et al 2021;Jennings et al 2021;Dryhurst et al 2020;Lim et al 2021), studies of trust in government and compliance with regard to government measures against COVID-19 have generally found that individuals with higher trust were more compliant (Bargain and Aminjonov 2020;Han et al 2021;Lalot et al 2022;Wright et al 2021;Olsen and Hjorth 2020;Lim et al 2021) and less hesitant towards vaccines during the pandemic (Jennings et al 2023;Syropoulos and Gkinopoulos 2023). Only a few studies do not confirm this pattern Clark et al 2020).…”
Section: System Trustmentioning
confidence: 99%